(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
Subarachnoid haemorrhage (SAH) due to spontaneous rupture of Berry aneurysm is the second most common cause of death after coronary artery disease. Intracranial aneurysms cause more than 50% cases of spontaneous subarachnoid haemorhage. Rupture can occur in young to middle aged persons during innocent activities such as jogging, sexual intercourse and sporting exertion. Here we are presenting a case of sudden natural death due to spontaneous rupture of an undiagnosed Berry aneurysm without any precipitating factors in a previously healthy person.